Energy performance, safety and durability of charcoal cooking stoves commonly used in West Africa: Benin case study - ZANNOU-TCHOKO, Stéphen Junior; BAKOUNOURE, Jihane; FAGBEMI, LATIF ADÉNIYI; EKOUEDJEN, Evrard Karol (My University, 2020)
The use of inefficient cooking stoves puts great pressure on the forests, as well as poorly secured cookers pose health risks to the users. Improving the energy efficiency of cookstoves reduces biomass consumption and thus the anthropogenic pressure on forests. This work aims to identify the best charcoal cooking stove(s) in terms of energy performance, safety and sustainability. The proposed approach combines the combined study of the energy performance, safety and durability of charcoal cooking cookers. A representative sample of five types of charcoal stoves commonly used in Benin is tested according to the requirements of the ISO 19867 standard. These are the square cooking stove, the circular cooking stove, the clay cooking stove, the rim cooking stove and the Nansu cooking stove. The results show two stoves with the best performance: The Nansu stove with a total energy efficiency of 27.44% and an output of 0.9 kW and the clay stove with a total energy efficiency of 25.11% and an output of 0.71 kW. These two stoves are made of clay, while the other three are made of metal. The clay stove offers the best safety with an overall average rating of 71.5 compared to 66.5 for the Nansu stove. The Nansu stove has better durability than the clay stove. This study thus contributes to the preservation of the environment and health through the recommendation of efficient, safe and durable charcoal cookers to be promoted.
Keywords: sector cooking stove; charcoal; energy performance; safety; durability